From Ethnobotany to Molecular Insight: Integrated In silico Discovery of DPP-4 Inhibitors from Stelechocarpus burahol (Blume) Fruit - Bintang Khoirun Nadzifah; Tutut Indah Sulistiyowati; Poppy Rahmatika Primandiri; Suparman; Seagames Waluyo; Sakuntala Ninkaew; Nor Hasniza Ibrahim; Agus_Muji Santoso (UNIVERSITAS PGRI MADIUN, 2026)
Diabetes mellitus remains a major global health challenge, encouraging the exploration of natural products as alternative therapeutics. Stelechocarpus burahol (kepel), an ethnobotanically significant Indonesian fruit traditionally consumed for its health benefits, represents a promising source of bioactive compounds. This study aimed to integrate ethnobotanical knowledge with molecular insights by identifying potential antidiabetic compounds using an in silico approach. A total of 66 phytochemical compounds were screened through drug-likeness, ADMET, and biological activity prediction, followed by molecular docking against Dipeptidyl Peptidase-4 (DPP-4) (PDB ID: 6B1E). The docking protocol was validated (RMSD 1.697 Å). Several phenolic compounds showed strong binding affinity, particularly gallocatechol (−8.4 kcal/mol), catechin (−8.2 kcal/mol), and 6-hydroxyluteolin (−8.1 kcal/mol), outperforming the native ligand. These findings highlight the potential of S. burahol as a natural source of DPP-4 inhibitors.